Measuring Education Quality in Global Rankings: What’s the Likelihood? - Altbach, Philip G.; Hazelkorn, Ellen (International Higher Education, 2018)
Can the global academic rankings measure teaching quality? The major academic rankings have been adding measures of teaching quality—such as teacher-student ratios. We argue that it is not possible, at least now, to accurately measure teaching quality in a cross-national context. We recommend that the rankings cease measuring something that cannot, at this time, be evaluated.